Nickel extraction from nickel laterites: Processes, resources, environment and cost - Zhen-fang Zhang; Wei-bo Zhang; Zhen-guo Zhang; Xiu-fa Chen (China Geology, 2025)
ABSTRACT: With the development of the new energy industry and the depletion of nickel sulfide ore resources, laterite nickel ore has become the main source of primary nickel, and nickel for power batteries has become a new growth point in consumption. This paper systematically summarizes the processes, parameters, products, recovery rates, environmental indicators, costs, advantages, disadvantages and the latest research progress of mainstream nickel extraction processes from laterite nickel ore. It also provides a comparative analysis of the environmental impact and economic efficiency of different nickel extraction processes. It is found that the current nickel extraction processes from laterite nickel ore globally for commercial production mainly include the RKEF process for producing ferronickel and the HPAL process for producing intermediate products. The former accounts for about 80% of laterite nickel ore production. Compared to each other, the investment cost per ton of nickel metal production capacity for the RKEF is about 43000$, with an operational cost of about 16000$ per ton of nickel metal and a total nickel recovery rate of 77%–90%. Its products are mainly used in stainless steels. For the HPAL process, the investment cost per ton of nickel metal production capacity is about 56000$, with an operational cost of about 15000 $ per ton of nickel metal and a total nickel recovery rate of 83%–90%. Its products are mainly used in power batteries. The significant differences between the two lies in energy consumption and carbon emissions, with the RKEF being 2.18 and 2.37 times that of the HPAL, respectively. Although the use of clean energy can greatly reduce the operational cost and environmental impact of RKEF, if RKEF is converted to producing high Ni matte, its economic and environmental performance still cannot match that of the HPAL and oxygen-enriched side-blown processes. Therefore, it can be inferred that with the increasing demand for nickel in power batteries, HPAL and oxygen-enriched side blowing processes will play a greater role in laterite nickel extraction.